Levers of Eco-Control: Linking Environmental Concern, Stakeholder Pressure in Predicting Green Behaviour - Selly Puspita Sari Sari; Fauzan Fuadi (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study investigates the influence of environmental concern and stakeholder pressure on green behavior in hospital medical waste management, with the Levers of Eco-Control (LoEC) as a mediating variable. The research emphasizes the importance of managerial control systems in translating environmental strategies into sustainable operational practices. Methodology: Data were obtained from 140 respondents directly involved in hospital waste management activities. The data were analyzed using the Structural Equation Modeling Partial Least Squares (SEM-PLS) method to test the relationships among environmental concern, stakeholder pressure, LoEC, and green behavior. Results: Stakeholder pressure has a significant positive effect on both LoEC and green behavior. LoEC strengthens green behavior and mediates the relationship between stakeholder pressure and environmentally responsible practices. Conversely, environmental concern does not exhibit a significant direct or indirect influence through LoEC. Conclusions: External stakeholder pressure and structured eco-control systems are more effective in encouraging sustainable behavior than individual awareness alone. The integration of LoEC enhances hospitals’ environmental accountability and compliance with sustainability standards. Limitations: By focusing on behavioral factors, this study underscores the centrality of these factors in enhancing the effectiveness of sustainable medical waste management practices. Contributions: This study extends the LoEC framework to the healthcare sector and provides theoretical and practical insights into how control-based mechanisms can institutionalize green behavior in medical waste management.